2013
DOI: 10.2119/molmed.2013.00034
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Inhibits Proliferation and Tumor Necrosis Factor α-Stimulated Activation of p38, c-Jun NH2-Terminal Kinase (JNK) and Akt in Rheumatoid Synovial Fibroblasts

Abstract: Synovial fibroblast proliferation is a hallmark of the invasive pannus in the rheumatoid joint. Activated protein C (APC) is a natural anticoagulant that exerts antiinflammatory and cyto-protective effects in various diseases via endothelial protein C receptor (EPCR) and proteinase-activated receptor (PAR)-mediated pathways. In this study, we investigated the effect and the underlying cellular signaling mechanisms of APC on proliferation of human rheumatoid synovial fibroblasts (RSFs). We found that APC stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
0
8
1
Order By: Relevance
“…It has been suggested that several signaling molecules, such as Akt and MAPKs, including p38, JNK, and ERK1/2, participate in controlling cell invasion (Julovi et al, ). In the present study, we found that EG‐VEGF facilitates trophoblast cell invasiveness, and we explored the downstream signaling in EG‐VEGF‐treated trophoblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that several signaling molecules, such as Akt and MAPKs, including p38, JNK, and ERK1/2, participate in controlling cell invasion (Julovi et al, ). In the present study, we found that EG‐VEGF facilitates trophoblast cell invasiveness, and we explored the downstream signaling in EG‐VEGF‐treated trophoblast cells.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest a role of APC/EPCR pathway in reducing metastasis via inhibition of tumor cell adhesion and transmigration (Bezuhly et al , 2009). In addition, it is reported that APC induces enhanced expression of p21 WAF1/CIP1 and p27 KIP1 in rheumatoid synovial fibroblasts (Julovi et al , 2013). As aforementioned, p21 WAF1/CIP1+ liver cell foci were increased after 4 weeks of TAA-promotion, and p21 WAF1/CIP1– liver cell foci were increased after 8 weeks of TAA-promotion (Tsuchiya et al , 2012), suggesting that APC plays a role in the facilitation of cellular senescence in liver cells, and its downregulation directs liver cells to begin the carcinogenic process.…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, p21 WAF1/CIP1+ liver cell foci were increased after 4 weeks of TAA-promotion, and p21 WAF1/CIP1– liver cell foci were increased after 8 weeks of TAA-promotion (Tsuchiya et al , 2012), suggesting that APC plays a role in the facilitation of cellular senescence in liver cells, and its downregulation directs liver cells to begin the carcinogenic process. In addition, it is also reported that APC downregulates tumor necrosis factor α-stimulated cell proliferation and activation of p38 mitogen-activated protein kinase (MAPK), c-Jun NH2-terminal kinase and AKT in rheumatoid synovial fibroblasts (Julovi et al , 2013). We previously found an increase of liver cell foci expressing AKT-signaling molecules and activated p38 MAPK by phosphorylation in a population of GST-P + foci produced by promotion with nongenotoxic hepatocarcinogens (Ichimura et al , 2010; Taniai et al , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumour cell cultures were established by explant growth of small fragments (≈1 mm) dissected from the PDAC tumour tissues, placed in DMEM (pH7.4) supplemented with 10% heat-inactivated FBS with 50 units/ml penicillin/streptomycin. Cultures were used after passage 3 to avoid residual contamination by macrophages [ 30 ]. All cultures were collected under identical growth and serum conditions.…”
Section: Methodsmentioning
confidence: 99%